The Politics of Visual Culture: 2010 Shanghai World Expo. - Wang, Lumay. (Tufts Archival Research Center, 2005)
Exhibitions, architecture, and maps all fall into the realm of visual culture, and each can transmit and convey specified messages. The politics of visual culture is integral to understanding how knowledge, taste, and power are formed. One should look at world expositions and in particular, the 2010 Shanghai World Expo, because the role of representation and the visual is augmented exponentially. Given China's fast economic growth, the Expo served as a huge opportunity for foreign nations to present their identities, their culture, and their products. This thesis explores how the Shanghai Expo demonstrates the power of the visual to manipulate, to guide, and to lead people's perceptions of their identity, their reality, and the world at large. It also examines the politics of representation. In particular the research focuses on European Union identity, the visual cohesiveness or lack thereof of the political and economic union, and the implications of the identity. Through in-depth visual analysis and aided by interviews, photographs, and other primary sources, this thesis critically examines international relations relevant to contemporary society.